Microfinance Digital Financial Services And Rural Farmers’ Welfare And Susceptibility To Poverty In Rural Ghana - Akantege, Raymond; Rahayu, Agus; Furqon, Chaerul; Dirgantari, Puspodewi (UNIVERSITAS PAKUAN, 2024)
Expanding access to the poor is a fundamental issue for Microfinance Institutions, although increasing the availability of credit is often viewed as a crucial element for achieving poverty reduction. Consequently, more trust has been reposed in the potentially game-changing effect of universal digital financial inclusion. However, there is little evidence linking digital financial inclusion to an individual's chance of poverty. The research assesses the influence of digital financial services on rural farmers' susceptibility to poverty in Ghana by employing data from 1050 rural farm households surveyed in selected communities in the Bono, Bono East and Bono Ahafo, Eastern and Ashanti Regions of Ghana. The Asset-Based Vulnerability model was used to measure the likelihood of future vulnerability to poverty of rural farmers. We found that farmers who make use of digital financial services are less vulnerable to risk. In addition, we demonstrate that the majority of these gains result from farmers' improved risk management abilities. Financial exclusion is a big issue in several developing countries, and Ghana's experience may be used to alleviate this problem.